2022
DOI: 10.1111/fare.12818
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of healthy marriage and relationship education for expectant and new mothers

Abstract: ObjectiveTo build the evidence base on healthy marriage and relationship education (HMRE) programs serving individual adults, this study examined the 1‐year impacts of the MotherWise program, which serves women with low incomes who are pregnant or have just had a baby.BackgroundDespite the increasing prevalence of HMRE programs serving individual adults, few studies have rigorously examined their effectiveness.MethodWomen were randomly assigned to either (a) an intervention group offered MotherWise (n = 512), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…Of particular interest to the present study, the longer term follow-up data show that there was not a significant impact on depression one or two-and-a-half years after enrollment (Patnaik et al, 2022; Patnaik & Wood, 2021). However, postpartum depression symptoms are most likely to emerge in the first few weeks after delivery (American College of Obstetrics and Gynecology, 2019; O’Hara & McCabe, 2013).…”
Section: The Present Studymentioning
confidence: 68%
See 3 more Smart Citations
“…Of particular interest to the present study, the longer term follow-up data show that there was not a significant impact on depression one or two-and-a-half years after enrollment (Patnaik et al, 2022; Patnaik & Wood, 2021). However, postpartum depression symptoms are most likely to emerge in the first few weeks after delivery (American College of Obstetrics and Gynecology, 2019; O’Hara & McCabe, 2013).…”
Section: The Present Studymentioning
confidence: 68%
“…The developer reviewed approximately 5 hr of audiotape of Within My Reach workshop sessions every 2 weeks to identify topics to discuss during biweekly check-in meetings with the program director and facilitators. Patnaik and Wood (2021) reported that facilitators demonstrated high treatment adherence and fidelity to the program.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 1-year after study enrollment, those assigned to the MotherWise program reported better relationship and conflict management skills, less approval of couple violence, greater relationship happiness, and more use of constructive conflict behaviors than those assigned to the no-treatment control group. In addition, those assigned to the MotherWise program had fewer unintended pregnancies in the year following enrollment than those in the control group (Patnaik & Wood, 2021). (For the current study, we used a subset of this sample and medical chart data collected independently.…”
Section: Introductionmentioning
confidence: 99%